Effect of solvent; enhancing the wettability and engineering the porous structure of a calcium phosphate/agarose composite for drug delivery. Issue 24 (15th March 2015) - Kolanthai, Elayaraja; Dikeshwar Colon, V. Sivaraj; Sindu, P. Abinaya; Chandra, V. Sarath; Karthikeyan, K. R.; Babu, M. Surendar; Sundaram, S. Meenakshi; Palanichamy, M.; Kalkura, S. Narayana
<x xml:space="preserve">Abstract</x> Porous 3D degradable hydrophilic ceramic–polymer composites were fabricated for tissue engineering and drug delivery applications.